Factors Influencing Nursing Interns' Engagement in Fall Prevention Activities in Saudi Arabia - Saeed Asiri; Ali Kerari (Nursing Open)
ABSTRACT Aim To assess the knowledge, attitudes and engagement of nursing interns regarding fall prevention activities during their internship within hospital settings. Design This study used a cross‐sectional design. Methods This was a cross‐sectional, descriptive, correlational study. A convenience sample of 187 nursing interns was recruited from three hospitals in Riyadh, Saudi Arabia. A questionnaire was administered to the participants to collect data on their demographics, knowledge, attitudes and engagement in fall prevention. The collected data were analysed using descriptive and inferential statistics. Results The participants exhibited insufficient knowledge, relatively negative attitudes and acceptable fall prevention engagement. There was a low‐to‐moderate positive association only between attitude and fall prevention engagement. Moreover, hierarchical multiple regression analysis showed that attitude was the only predictor for fall prevention engagement. Conclusion Fall prevention is an important subject that needs more attention from nursing programmes in universities and preceptorship programmes in hospitals to enhance nursing interns' attitudes, knowledge and practices in this regard. Relevance to Clinical Practice The findings of this research could be beneficial for clinical coordinators and faculty members to enhance nursing interns' engagement in preventing falls among at‐risk patients. Patient or Public Contribution Participants were not involved in the design, conduct, reporting or dissemination of this research.